Level of Motivation for Academic Achievement Among Gifted Students in Ajloun Governorate in Light of Some Variables - Nawasreh, Faisal; Gharaibeh, Mahmoud; AL Momani, Randa Mousa; aleid, wafaa; Alqudah, Rabha Adnan; Alkouri, Zaid; Tawalbeh, Maria Salih; Al-Kharabsheh, Omar Mohammed; Daradkah, Amjad Mahmoud (Journal of Posthumanism, 2025)
The study aimed to reveal on Motivation for achieve amendment for gifted students from the school's students at Ajloun Governorate in the light of some demographic variables (Gender, grade, and educational level of father and mother, and the economic level of the family). Descriptive, correlational, analytical approach To achieve the study objectives, used a scale of Motivation . And the developed it to suit the study sample. And the indications of validity and reliability were high for this scale, and the sample consists of (127) students from Gifted students who were selected randomly stratified from upper primary and secondary classes, and the data was analyzed by finding arithmetic means, Standard deviations, the value of (T) and One-way analysis of variance. The results of the study showed that the level of Motivation for achieve amendment among gifted students was high, and there were statistically significant differences at (α≤ 0.05) at the degrees level of Motivation of achievement among gifted students for grade variable in favor of seventh grade. And there weren't any statistically significant differences at gender, educational level of parents and economic level of the family, The results also showed that there were a positive correlation Statistical significance at the level (α≤ 0.05) between motivation for achievement and academic achievement.